THE EFFECT OF SERVICE QUALITY ON PATIENT SATISFACTION AT PANEMBAHAN SENOPATI REGIONAL PUBLIC HOSPITAL BANTUL REGENCY SPECIAL REGION OF YOGYAKARTA - Susatyo Herlambang; Putri Karnihajir; Suliantoro (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2026)
This study aims to determine the effect of service quality on patient satisfaction at Panembahan Senopati Regional Public Hospital, Bantul Regency, Special Region of Yogyakarta. The service quality variable is measured using five indicators, namely tangibles, reliability, responsiveness, assurance, and empathy, along with the patient satisfaction variable. This research employs a descriptive quantitative method. The population in this study consists of 25,022 patients, with a sample size of 100 respondents determined using the Slovin formula. Data collection techniques were carried out through direct observation and the distribution of questionnaires using a Likert scale. The data analysis method used is simple linear regression with the assistance of SPSS version 26. The results of this study indicate that service quality has a positive effect on patient satisfaction. This means that the better the service quality provided, the higher the level of patient satisfaction at Panembahan Senopati Regional Public Hospital, Bantul Regency, Special Region of Yogyakarta.